Linking High School Students’ Achievement Goal Orientations With Their Competence Beliefs and Their Perception of Teachers’ Emotional Support During the COVID-19 Pandemic - Smith, Jonathan; Nadeau, Marie-France; Archambault, Isabelle; Guimond, Fanny-Alexandra; St-Amand, Jérôme; Fitzpatrick, Caroline; Gagnon, Mathieu (Frontiers in Education, 2022)
Due to the COVID-19 pandemic, adolescents have experienced limitations in their everyday activities. Consequently, their mental health has become an area of concern. However, there has been much less of a focus on the factors and mechanisms contributing to how they have approached their various academic activities during the pandemic. The current study fills this gap by investigating associations between adolescents’ competence beliefs and perception of teachers’ emotional support and their achievement goals (mastery, performance, and work avoidance) at the onset of the second wave of this pandemic in Canada. Participants were 90 Canadian high school adolescents in grades 9 and 10 and they were surveyed in November of 2020. Data were analyzed using multiple regression and mediation analyses. Among the most salient results, competence beliefs were found to predict achievement goals, above and beyond teachers’ emotional support, and these beliefs were significantly and positively associated with mastery and performance orientation, and marginally and negatively associated with work avoidance orientation. Results also showed that competence beliefs mediated the association between teachers’ emotional support and the mastery goal orientation. These findings are discussed in light of relevant pre-pandemic evidence about the role of competence beliefs and teachers’ emotional support on achievement goal orientations.